Rozpad świata i podmiotu – czyli o pewnej (po-)nowoczesnej opowieści - Musielak, Łukasz (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2008)
The aim of this article is attempt to reconstruct the model of Western Culture, which appears on field of contemporary philosophy of culture. This view basis on the division of the culture into 3 periods: pre-modernity, modernity and post-modernity. Modernity is initiated with intensive increase of rationalization, disenchantment of the world, as well as with faith in reason and improvement. Post-modernity stems from disappointment of reason and fear of consequences of technical progress. Reason and Progress are treated as substitute for traditional myth and religions. Pre-modernity are background for those analyses. Nowadays this is the model of interpretation for social and intellectual events observed in Western culture. That model deals with general and permanent crisis of culture. The essence of this crisis is fragmentation of the human world (break-up of fundamentals of philosophical and scientific inquiry as well as everyday morality) and 'myself'.